A preparation method of a composite all-solid-state electrolyte based on electrostatic dissolution and blowing technology
Patent Information
- Application Number
- CN202210807394.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-11
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-07-11
AI Technical Summary
然而至今为止,中空结构的纤维的引入较少,Gd掺杂 SnO2中空结构纳米纤维作为填料至今没有报道
[0013]由于采用以上技术方案,本发明的全固态锂离子电池具有以下特点:
Smart Images

Figure CN115332613B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a composite all-solid-state electrolyte based on electrostatic melt blowing technology, belonging to the technical field of all-solid-state lithium-ion batteries. Background Technology
[0002] With the scarcity of natural energy and the improvement of people's living standards, there is a greater demand for electric components. However, in recent years, battery safety issues have occurred frequently. Accelerating the development of a safe, efficient, and sustainable battery is currently a pressing matter. Today, almost all lithium-ion batteries used in applications employ liquid electrolytes. However, the reaction between the liquid electrolyte and the electrodes often reduces the battery's cycle stability. Moreover, liquid electrolytes have limited energy density and poor thermal and chemical stability. Because liquid electrolytes are flammable, they are prone to leakage during storage and use, posing significant safety concerns. Replacing flammable organic liquid electrolytes with non-flammable all-solid-state electrolytes can not only completely solve the leakage problem and greatly improve battery safety performance, but also suppress side reactions, resulting in higher energy density.
[0003] As a key component of all-solid-state lithium-ion batteries, solid electrolytes can be divided into three types: inorganic solid electrolytes, solid polymer electrolytes, and composite solid electrolytes. Inorganic solid electrolytes typically exhibit excellent lithium-ion conductivity and migration, which is highly beneficial for improving the overall performance of all-solid-state batteries. However, inorganic solid electrolytes are usually prepared using repeated solid-state sintering and powder pressing methods, resulting in high cost and long processing time. Furthermore, inorganic solid electrolytes suffer from high brittleness and poor interfacial compatibility between the electrolyte and electrodes, significantly hindering their further development. Solid polymer electrolytes based on polymer matrices and lithium salts have relatively simple and convenient processes and lower costs. The electrolyte membrane can be prepared using doctor blade or casting methods, showing potential for industrial-scale production. Solid polymer electrolytes have good film-forming properties and advantages such as high flexibility and good interfacial compatibility with electrodes. However, solid polymer electrolytes also have some drawbacks. The most representative polymer-based electrolyte is polyethylene oxide (PEO). First, Li... + The transport of [atom] mainly occurs in the amorphous region through coordination and dissociation with oxygen atoms in the material. However, PEO has a relatively high crystallinity, which is beneficial for Li [material]. +The transfer of lithium ions is highly unfavorable. This defect leads to low lithium-ion conductivity. Secondly, the coexistence of crystalline and amorphous phases in PEO polymers causes uneven migration of lithium ions in solid polymer electrolytes, ultimately leading to the growth of lithium dendrites. However, PEO electrolytes have poor mechanical strength. When lithium dendrites grow to a certain extent, they may pierce the PEO electrolyte, causing a short circuit in the working battery. These problems limit its further application in lithium-ion batteries. In recent years, researchers have focused on preparing composite solid electrolytes by adding inorganic nanofillers to the polymer matrix to improve electrolyte performance. In particular, composite solid electrolytes prepared by adding fillers with high lithium-ion conductivity to solid polymer electrolytes have a wide electrochemical stability window, excellent ionic conductivity, good flexibility, and a simple synthesis method. At the same time, composite solid electrolytes have good compatibility with electrodes. Therefore, composite solid electrolytes have attracted widespread attention. On the one hand, adding inorganic nanofillers to the polymer matrix can reduce the crystallinity of PEO. On the other hand, there is a Lewis acid-base interaction between the introduced inorganic nanofillers and lithium salts. Numerous studies have shown that Lewis acid-base model interactions strongly support the increase in ionic conductivity. In particular, the anionic groups in lithium salts are adsorbed onto the surface of inorganic nanoparticles, significantly promoting the dissociation of lithium salts and releasing more Li₂. + Meanwhile, the surface of inorganic nanofillers provides pathways conducive to Li+ transfer. Studies have found that the introduction of inorganic ceramic fillers can not only effectively improve ionic conductivity and mechanical properties, but also enhance the thermal stability of composite solid electrolytes.
[0004] The concept of introducing nanomaterials into solid-state electrolytes (SSEs) was proposed in 1982. Through continuous exploration, researchers realized that adding one-dimensional ceramic fillers to solid-state polymer electrolytes significantly improves the conductivity of lithium ions. This is because, compared to nanoparticles, one-dimensional nanofillers can provide long-distance ordered ion transport channels. Simultaneously, electrochemical stability and mechanical properties are improved. Due to the high strength and flame-retardant properties of nanowire fillers, the mechanical and flame-retardant properties of composite solid-state electrolytes are also enhanced. Adding one-dimensional ceramic nanofillers to solid-state polymer electrolytes can effectively improve the ionic conductivity of lithium ions, thereby effectively improving the electrochemical and mechanical performance of the battery. However, to date, the introduction of hollow fiber structures is relatively rare, and Gd-doped SnO2 hollow nanofibers as fillers have not yet been reported. Summary of the Invention
[0005] To address the problems existing in the aforementioned background technology, the purpose of this invention is to propose a novel electrostatic melt-blowing process for preparing Gd-doped SnO2 nanofibers with hollow structures, and to successfully prepare a PEO-based composite all-solid-state electrolyte film with a thickness of only 120 μm using these nanofibers as fillers. This method can reduce the crystallinity of the polymer, increase the ionic conductivity and mechanical properties of the composite all-solid-state electrolyte, effectively suppress the growth of lithium dendrites, and improve the electrochemical performance of the all-solid-state electrolyte.
[0006] 1. To achieve the above objectives, the present invention provides a composite all-solid-state electrolyte based on electrostatic meltblowing technology, characterized by comprising the following steps:
[0007] (1) Preparation of spinning solution of Gd-doped SnO2 precursor: Anhydrous ethanol, DMF, PVP K90, gadolinium nitrate and crystalline tin tetrachloride were mixed evenly in a certain proportion to prepare spinning solution.
[0008] (2) Nonwoven process of Gd-doped SnO2 nanofiber precursor: The spinning solution prepared in step (1) is used to prepare Gd-doped SnO2 nanofiber precursor by electrostatic melt blowing device.
[0009] (3) High-temperature calcination treatment of Gd-doped SnO2 nanofiber precursor: The precursor Gd-doped SnO2 nanofiber prepared in step 2) is calcined in air at a certain temperature to obtain hollow Gd-doped SnO2 nanofiber.
[0010] (4) Preparation of all-solid-state composite electrolyte: The hollow Gd-doped SnO2 nanofibers prepared in step 3) were mixed with PEO, LiTFSI and acetonitrile in a certain proportion and stirred evenly. The evenly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50°C for 24 h, and then hot-pressed at 50°C for 30 min to obtain a 120 μm composite all-solid-state electrolyte.
[0011] 2. The all-solid composite electrolyte prepared by electrostatic melting and blowing technology as described in claim 1 is characterized in that: the heating rate is 5°C per minute to 600-1000°C and held at that temperature for 2 hours.
[0012] 3. The all-solid composite electrolyte prepared by electrostatic melt blowing technology as described in claim 1 or 2, characterized in that: the proportion of Gd-doped SnO2 nanofibers in the all-solid composite electrolyte is 5%, 10%, and 15%.
[0013] Due to the adoption of the above technical solutions, the all-solid-state lithium-ion battery of the present invention has the following characteristics:
[0014] 1) For electrolytes, Gd-doped SnO2 filler enhances the movement of PEO chain segments, reduces the glass transition temperature of PEO, and improves the ionic conductivity of electrolytes.
[0015] 2) There are a large number of oxygen vacancies in Gd-doped SnO2.
[0016] 3) The Lewis acid-base interaction between lithium salt and Gd-doped SnO2 nanofiber filler promotes the dissociation of lithium salt. Compared with particulate oxide fillers, hollow and long-range ordered fibers can provide a certain transport channel for the conduction of lithium ions in the periphery, thus improving lithium ion conduction.
[0017] 4) SnO2 has a good affinity for lithium and can suppress the formation of lithium dendrites.
[0018] The above four characteristics enable the prepared all-solid-state lithium-ion battery to have superior electrochemical performance and practicality in high-voltage safe all-solid-state lithium metal batteries.
[0019] This invention provides a method for preparing a composite all-solid electrolyte based on electrostatic melt blowing technology. Attached Figure Description
[0020] Figure 1 Fabrication process for composite all-solid-state electrolytes and assembled all-solid-state batteries based on electrostatic melt-blowing technology.
[0021] Figure 2(a) is a SEM image of Gd-doped SnO2 nanofibers calcined at 600℃.
[0022] Figure 2(b) shows the SEM image of Gd-doped SnO2 nanofibers calcined at 800℃.
[0023] Figure 2(c) shows the SEM image of Gd-doped SnO2 nanofibers calcined at 1000℃.
[0024] Figure 3 Arrhenius curves of pure PEO-LiTFSI electrolyte, 5% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte, 10% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte and 15% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte at 30-70℃.
[0025] Figure 4 Electrochemical impedance spectroscopy (EIS) diagrams before and after cycling of lithium / lithium iron phosphate batteries assembled based on pure PEO-LiTFSI electrolyte and 10% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte. Detailed Implementation
[0026] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0027] Example 1
[0028] (1) In this invention, it is first necessary to prepare a Gd-doped SnO2 precursor spinning solution. The specific steps are as follows: 4.5g of PVP K90 powder is added to a mixture of 12g of anhydrous ethanol and 24g of DMF, and stirred at room temperature for 30min until the solution is clear and transparent; and at 60℃, 5.4g of tin tetrachloride and 1.2g of gadolinium nitrate are dissolved in the solution, stirred for 2h until completely dissolved, and left to stand for a period of time to eliminate bubbles.
[0029] (2) Add the spinning solution prepared in step (1) above to the electrostatic meltblowing device. The extrusion speed of the spinning solution is 0.6 mL / min. -1 The spinning needle has an inner diameter of 0.8 mm and is 80 cm away from the fiber membrane receiving device. The spinning voltage is 40 kV, and the outlet pressure is 0.1 MPa. Before reaching the collecting plate, the spinning liquid jet is fully stretched under the action of rapid airflow and electrostatic repulsion due to the rapid airflow and electrostatic repulsion, ultimately forming precursor nanofibers on the collecting plate. Collecting the nanofibers on the collecting plate yields precursor Gd-doped SnO2 nanofibers.
[0030] (3) The precursor Gd-doped SnO2 nanofibers prepared in step (2) are heated to 800°C in air at a heating rate of 5°C per minute and held for 2 hours to obtain hollow Gd-doped SnO2 nanofibers.
[0031] (4) The hollow Gd-doped SnO2 nanofibers (mass fraction of 5 wt.%) prepared in step (3) were mixed with PEO, LiTFSI, and acetonitrile (the molar ratio of [EO] and [Li] in PEO and LiTFSI was 12:1) and stirred for 36 h. The uniformly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50 °C for 24 h, and then hot-pressed at 50 °C for 30 min to obtain a 120 μm composite all-solid electrolyte.
[0032] Example 2
[0033] (1) In this invention, it is first necessary to prepare a Gd-doped SnO2 precursor spinning solution. The specific steps are as follows: 4.5g of PVP K90 powder is added to a mixture of 12g of anhydrous ethanol and 24g of DMF, and stirred at room temperature for 30min until the solution is clear and transparent; and at 60℃, 5.4g of tin tetrachloride and 1.2g of gadolinium nitrate are dissolved in the solution, stirred for 2h until completely dissolved, and left to stand for a period of time to eliminate bubbles.
[0034] (2) Add the spinning solution prepared in step (1) above to the electrostatic meltblowing device. The extrusion speed of the spinning solution is 0.6 mL / min. -1 The spinning needle has an inner diameter of 0.8 mm and is 80 cm away from the fiber membrane receiving device. The spinning voltage is 40 kV, and the outlet pressure is 0.1 MPa. Before reaching the collecting plate, the spinning liquid jet is fully stretched under the action of rapid airflow and electrostatic repulsion due to the rapid airflow and electrostatic repulsion, ultimately forming precursor nanofibers on the collecting plate. Collecting the nanofibers on the collecting plate yields precursor Gd-doped SnO2 nanofibers.
[0035] (3) The precursor Gd-doped SnO2 nanofibers prepared in step (2) are heated to 800°C in air at a heating rate of 5°C per minute and held for 2 hours to obtain hollow Gd-doped SnO2 nanofibers.
[0036] (4) The hollow Gd-doped SnO2 nanofibers (mass fraction of 10 wt.%) prepared in step (3) were mixed with PEO, LiTFSI, and acetonitrile (the molar ratio of [EO] and [Li] in PEO and LiTFSI was 12:1) and stirred for 36 h. The uniformly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50 °C for 24 h, and then hot-pressed at 50 °C for 30 min to obtain a 120 μm composite all-solid electrolyte.
[0037] Example 3
[0038] (1) In this invention, it is first necessary to prepare a Gd-doped SnO2 precursor spinning solution. The specific steps are as follows: 4.5g of PVP K90 powder is added to a mixture of 12g of anhydrous ethanol and 24g of DMF, and stirred at room temperature for 30min until the solution is clear and transparent; and at 60℃, 5.4g of tin tetrachloride and 1.2g of gadolinium nitrate are dissolved in the solution, stirred for 2h until completely dissolved, and left to stand for a period of time to eliminate bubbles.
[0039] (2) Add the spinning solution prepared in step (1) above to the electrostatic meltblowing device. The extrusion speed of the spinning solution is 0.6 mL / min. -1 The spinning needle has an inner diameter of 0.8 mm and is 80 cm away from the fiber membrane receiving device. The spinning voltage is 40 kV, and the outlet pressure is 0.1 MPa. Before reaching the collecting plate, the spinning liquid jet is fully stretched under the action of rapid airflow and electrostatic repulsion due to the rapid airflow and electrostatic repulsion, ultimately forming precursor nanofibers on the collecting plate. Collecting the nanofibers on the collecting plate yields precursor Gd-doped SnO2 nanofibers.
[0040] (3) The precursor Gd-doped SnO2 nanofibers prepared in step (2) are heated to 800°C in air at a heating rate of 5°C per minute and held for 2 hours to obtain hollow Gd-doped SnO2 nanofibers.
[0041] (4) The hollow Gd-doped SnO2 nanofibers (mass fraction of 15 wt.%) prepared in step (3) were mixed with PEO, LiTFSI, and acetonitrile (the molar ratio of [EO] and [Li] in PEO and LiTFSI was 12:1) and stirred for 36 h. The uniformly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50 °C for 24 h, and then hot-pressed at 50 °C for 30 min to obtain a 120 μm composite all-solid electrolyte.
[0042] Example 4
[0043] (1) In this invention, it is first necessary to prepare a Gd-doped SnO2 precursor spinning solution. The specific steps are as follows: 4.5g of PVP K90 powder is added to a mixture of 12g of anhydrous ethanol and 24g of DMF, and stirred at room temperature for 30min until the solution is clear and transparent; and at 60℃, 5.4g of tin tetrachloride and 1.2g of gadolinium nitrate are dissolved in the solution, stirred for 2h until completely dissolved, and left to stand for a period of time to eliminate bubbles.
[0044] (2) Add the spinning solution prepared in step (1) above to the electrostatic meltblowing device. The extrusion speed of the spinning solution is 0.6 mL / min. -1 The spinning needle has an inner diameter of 0.8 mm and is 80 cm away from the fiber membrane receiving device. The spinning voltage is 40 kV, and the outlet pressure is 0.1 MPa. Before reaching the collecting plate, the spinning liquid jet is fully stretched under the action of rapid airflow and electrostatic repulsion due to the rapid airflow and electrostatic repulsion, ultimately forming precursor nanofibers on the collecting plate. Collecting the nanofibers on the collecting plate yields precursor Gd-doped SnO2 nanofibers.
[0045] (3) The precursor Gd-doped SnO2 nanofibers prepared in step (2) are heated to 600°C in air at a heating rate of 5°C per minute and held for 2 hours to obtain hollow Gd-doped SnO2 nanofibers.
[0046] (4) The hollow Gd-doped SnO2 nanofibers (mass fraction of 10 wt.%) prepared in step (3) were mixed with PEO, LiTFSI, and acetonitrile (the molar ratio of [EO] and [Li] in PEO and LiTFSI was 12:1) and stirred for 36 h. The uniformly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50 °C for 24 h, and then hot-pressed at 50 °C for 30 min to obtain a 120 μm composite all-solid electrolyte.
[0047] Example 5
[0048] (1) In this invention, it is first necessary to prepare a Gd-doped SnO2 precursor spinning solution. The specific steps are as follows: 4.5g of PVP K90 powder is added to a mixture of 12g of anhydrous ethanol and 24g of DMF, and stirred at room temperature for 30min until the solution is clear and transparent; and at 60℃, 5.4g of tin tetrachloride and 1.2g of gadolinium nitrate are dissolved in the solution, stirred for 2h until completely dissolved, and left to stand for a period of time to eliminate bubbles.
[0049] (2) Add the spinning solution prepared in step (1) above to the electrostatic meltblowing device. The extrusion speed of the spinning solution is 0.6 mL / min. -1 The spinning needle has an inner diameter of 0.8 mm and is 80 cm away from the fiber membrane receiving device. The spinning voltage is 40 kV, and the outlet pressure is 0.1 MPa. Before reaching the collecting plate, the spinning liquid jet is fully stretched under the action of rapid airflow and electrostatic repulsion due to the rapid airflow and electrostatic repulsion, ultimately forming precursor nanofibers on the collecting plate. Collecting the nanofibers on the collecting plate yields precursor Gd-doped SnO2 nanofibers.
[0050] (3) The precursor Gd-doped SnO2 nanofibers prepared in step (2) are heated to 1000°C in air at a heating rate of 5°C per minute and held for 2 hours to obtain hollow Gd-doped SnO2 nanofibers.
[0051] (4) The hollow Gd-doped SnO2 nanofibers (mass fraction of 10 wt.%) prepared in step (3) were mixed with PEO, LiTFSI, and acetonitrile (the molar ratio of [EO] and [Li] in PEO and LiTFSI was 12:1) and stirred for 36 h. The uniformly stirred solution was poured onto a polytetrafluoroethylene plate, dried in a vacuum drying oven at 50 °C for 24 h, and then hot-pressed at 50 °C for 30 min to obtain a 120 μm composite all-solid electrolyte.
[0052] Performance testing:
[0053] The composite all-solid electrolyte disclosed in this application is characterized by the preparation of a PEO-based composite all-solid electrolyte using hollow Gd-doped SnO2 nanofibers as fillers. This composite all-solid electrolyte has good ionic conductivity, high mechanical strength, and excellent electrochemical stability. All-solid lithium-ion batteries assembled using the composite all-solid electrolyte of this application have excellent electrochemical performance and cycle life.
[0054] Figure 1 This application describes a fabrication process for a composite all-solid-state electrolyte and its assembled all-solid-state battery based on electrostatic melt-blowing technology. The composite all-solid-state electrolyte is prepared using electrostatic melt-blowing technology. By adjusting the voltage and gas pressure, the state of the solution reaching the collection plate can be precisely controlled. Due to the effects of rapid airflow and a high-voltage electrostatic field, the spinning solution jet can be fully stretched under the influence of rapid airflow and electrostatic repulsion, ultimately forming precursor Gd-doped SnO2 nanofibers on the collection plate. The precursor Gd-doped SnO2 nanofibers are then calcined at high temperature to obtain hollow Gd-doped SnO2 nanofibers, which are then used as fillers to prepare a 120 μm PEO-based composite all-solid-state electrolyte using solution casting and hot-pressing processes. The electrolyte obtained by solution casting easily forms a tight interface with the electrodes, thereby improving the interfacial compatibility between internal battery components. The subsequent hot-pressing process at 50°C produces a uniformly thick electrolyte film. Finally, this composite all-solid-state electrolyte is matched with a lithium metal anode and a LiFePO4 cathode to assemble an all-solid-state lithium-ion battery.
[0055] Figures 2(a), 2(b), and 2(c) show the morphology of Gd-doped SnO2 nanofibers at different calcination temperatures. It can be seen that the fibers at 600℃ have fewer hollow structures, while those at 800℃ exhibit better hollow structure morphology. The fiber morphology at 1000℃ is poor, possibly due to the fibers' high brittleness; the excessively high calcination temperature causes fiber breakage. This demonstrates that a calcination temperature of 800℃ results in better fiber morphology and the presence of a hollow structure.
[0056] Next, the ionic conductivity of three all-solid polymer electrolytes was tested to compare the effects of different compositions and processing techniques on the ionic conductivity of the fiber membranes.
[0057] The specific testing method for ionic conductivity was as follows: A CHI 660D electrochemical workstation was used. The battery adopted a structure of negative electrode shell-spring sheet-steel sheet-all-solid-state composite electrolyte-steel sheet-positive electrode shell. The grouping conditions were controlled at temperatures of 30℃, 40℃, 50℃, 60℃, and 70℃. The open-circuit voltage was set, and the high-frequency and low-frequency values were adjusted to 10... 6 Hz and 0.01Hz, with the amplitude controlled at 0.005A.
[0058] The lithium-ion conductivity value (σ) is calculated according to the following formula (1):
[0059]
[0060] In the formula, σ represents the ionic conductivity, R represents the resistance of the tested sample (Ω), L represents the thickness of the electrolyte (μm), and S represents the effective contact area between the intermediate spacer and the solid electrolyte (cm²). 2 ).
[0061] Figure 3 Arenius curves for composite all-solid-state electrolytes with different filler ratios are shown in the temperature range of 30℃ to 70℃. The effect of different filler ratios on the ionic conductivity of the composite solid-state electrolytes was compared by studying the Arenius curves of pure PEO-LiTFSI electrolyte, 5% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte, 10% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte, and 15% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte. The results show that the ion transport rate in the composite all-solid-state electrolyte with added filler in this application is faster, significantly higher than that of the pure PEO-LiTFSI electrolyte. The addition of Gd-doped SnO2 nanofibers with a high aspect ratio and hollow structure enhances the movement of PEO segments, lowers the glass transition temperature of PEO, and improves the ionic conductivity of the electrolyte.
[0062] Figure 4 The figure shows the electrochemical impedance spectroscopy (EIS) diagrams of the lithium / lithium iron phosphate (Li / LiFePO4) battery before and after cycling. It can be seen from the figure that the 10% Gd-doped SnO2 nanofiber-PEO-LiTFSI electrolyte has a lower impedance compared to the pure PEO-LiTFSI electrolyte. The low impedance of the Li / 10% Gd-doped SnO2 nanofiber-PEO-LiTFSI / LiFePO4 battery indicates good interfacial compatibility between the Gd-doped SnO2 nanofiber composite electrolyte and the electrode, mainly due to the excellent flexibility and high ionic conductivity of the electrolyte itself.
[0063] Example 1 is the preferred embodiment of this application, and Examples 2-5 also exhibited the same performance characteristics after the above performance tests. Therefore, in summary, Gd-doped SnO2 filler improves the ionic conductivity of the electrolyte, suppresses the formation of lithium dendrites, and contains a large number of oxygen vacancies. The Lewis acid-base interaction between the lithium salt and the Gd-doped SnO2 nanofiber filler promotes the dissociation of the lithium salt. Compared with particulate oxide fillers, hollow and long-range ordered fibers can provide a certain transport channel for the conduction of peripheral lithium ions, thus improving lithium ion conduction. The composite all-solid-state electrolyte of this application, due to its electrostatic melt-blowing process, endows the electrolyte with high ionic conductivity, high mechanical strength, and excellent electrochemical stability, and has sufficient ability to suppress lithium dendrite growth, thereby improving the performance of all-solid-state lithium-ion batteries.
Claims
1. A method for preparing a composite all-solid-state electrolyte based on electrostatic melt-blowing technology, characterized in that, Includes the following steps: (1) Preparation of spinning solution of Gd-doped SnO2 precursor: Anhydrous ethanol, DMF, PVP K90, gadolinium nitrate and crystalline tin tetrachloride were mixed evenly in a certain proportion to prepare spinning solution. (2) Nonwoven process of Gd-doped SnO2 nanofiber precursor: The spinning solution prepared in step (1) is used to prepare Gd-doped SnO2 nanofiber precursor by electrostatic melt blowing device. (3) High-temperature calcination treatment of Gd-doped SnO2 nanofiber precursor: The precursor Gd-doped SnO2 nanofiber prepared in step 2) is calcined in air at a certain temperature to obtain hollow Gd-doped SnO2 nanofiber. The heating and calcination process involves heating at a rate of 5°C per minute to 600-1000°C and holding at that temperature for 2 hours. (4) Preparation of all-solid composite electrolyte: The hollow Gd-doped SnO2 nanofibers prepared in step 3) are mixed with PEO, LiTFSI and acetonitrile in a certain proportion and stirred evenly. The evenly stirred solution is poured onto a polytetrafluoroethylene plate and dried in a vacuum drying oven at 50°C for 24 hours. Then, it is hot-pressed at 50°C for 30 minutes to obtain a composite all-solid electrolyte with a thickness of 120 μm.
2. The preparation method of the composite all-solid-state electrolyte based on electrostatic meltblowing technology as described in claim 1, characterized in that: The mass ratio of the Gd-doped SnO2 nanofibers in the all-solid composite electrolyte is 5%, 10%, or 15%.
Citation Information
Patent Citations
Preparation method of core-shell structure electrospinning nanofiber-ceramic nanowire-based all-solid-state composite electrolyte
CN113745643A
Preparation method of spiny inorganic nanofiber composite all-solid-state electrolyte
CN114069023A